DISTANCE LEARNING OPPORTUNITIES, FEATURES AND ALGORITHM OF MOODLE TECHNOLOGY IN THE LEARNING PROCESS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Although the use of distance learning in the learning process is not a new method, the purpose of the choice of the subject is currently used in all higher education institutions in extracurricular education, in pandemic conditions in all types of education